Optimal coalition structure generation strategy in multi-task concurrent edge computing environment - Shuxu ZHAO; Ping WEI; Xiaolong WANG (Tongxin xuebao)
A discrete recent past-position updating strategy based m-ary discrete particle swarm optimization (MDPSO-DRPPUS) algorithm was proposed for the problem of large search space and low efficiency when solving the optimal coalition structure.First, the coalition structure with index-based was coded.Then, the multi-objective optimization problem was transformed into an eigenvalue function of the coalition structure.Finally, the optimal coalition structure was searched by using the MDPSO-DRPPUS algorithm.Experiments show that compared with the m-ary discrete particle swarm optimization (MDPSO) algorithm and genetic algorithm (GA), the proposed algorithm dramatically reduces the average running time, and improves the efficiency and equilibrium of the coalition structure and task completion efficiency of edge nodes.